DYSTOCIA DUE TO CONJOINED HEADS IN A PRIMIPAROUS BUFFALO - RAO TALLURI, THIRUNIALA; PRASAD, B CHANDRA; ARANGASAMY, A (The Indian Journal of Animal Reproduction, 2023)
Present report records a rare case of conjoined heads causing dystocla and its clinical management in aprimiparous buffalo.
Keywords: Conjoined Heads; Fetal monster; Dystocia; Buffalo